A proposal to improve gene expression analysis. Issue 1 (15th January 2022) - Kerachian, Mohammad Amin; Azghandi, Marjan; Thiery, Jean Paul
Abstract: Gene expression profiling is commonly used to define molecular subtypes in cancers and gene sets can be identified as prognostic indicators or as potential biomarkers. Reverse transcription‐quantitative real‐time polymerase chain reaction is commonly used to measure relative changes in gene transcript messenger RNA levels. However, given target gene expression levels are inconstantly reported in the literature. The variable quantification of the gene expression level could be affected by intra/intergenic noncoding RNAs. To overcome this problem, we suggest the analysis be performed using at least two sets of primers, which are designed in two different regions of the target gene.